2013
DOI: 10.1093/abbs/gms117
|View full text |Cite
|
Sign up to set email alerts
|

Earle's balanced salts solution and rapamycin differentially regulate the Bacillus Calmette-Guérin-induced maturation of human dendritic cells

Abstract: Autophagy has been shown to enhance the efficacy of the Bacillus Calmette-Guérin (BCG) vaccine by increasing the peptide presentation of dendritic cells (DCs). Earle's balanced salts solution (EBSS) is a saline solution with physiological pH which is often used to induce autophagy, while rapamycin is a pharmacological reagent used for autophagy induction. In the present study, we studied the effect of EBSS and rapamycin on the maturation of DCs infected with BCG. The phenotype and function of the DCs were asse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 29 publications
(37 reference statements)
1
2
0
Order By: Relevance
“…A large number of studies showed that multiple components of BCG, such as cell wall [24], DNA fraction [25], and heat shock proteins [26], could activate DCs, and thus induce CTLs response. Consistent with previous research [27], we chose an MOI of 1 to stimulate DCs, and found that the markers of mature DCs were upregulated significantly. In addition, BCG-stimulated DCs promoted proliferation of autologous T cells.…”
Section: Discussionsupporting
confidence: 62%
“…A large number of studies showed that multiple components of BCG, such as cell wall [24], DNA fraction [25], and heat shock proteins [26], could activate DCs, and thus induce CTLs response. Consistent with previous research [27], we chose an MOI of 1 to stimulate DCs, and found that the markers of mature DCs were upregulated significantly. In addition, BCG-stimulated DCs promoted proliferation of autologous T cells.…”
Section: Discussionsupporting
confidence: 62%
“…The protective effects of autophagy during chronic ethanol consumption were further confirmed using the autophagy activator Earle's balanced salt solution (EBSS). 38 SalA and EBSS treatment reversed ethanol-induced cell injury ( Fig. 3c ).…”
Section: Resultsmentioning
confidence: 75%
“…How autophagy is induced might however be important. For example by inducing autophagy with Earle's balanced salts solution (EBSS) in BCG infected DCs, cytokine production was promoted and expression of HLA-DR was increased, while treatment with rapamycin had the opposite effect (225). Since rapamycin is a rather poor inducer of autophagy in mammalian cells with its effect depending on cell type (212), we additionally used Torin1 in our experiments (Paper I).…”
Section: Discussionmentioning
confidence: 99%